Role of Citrate and NaBr at the Surface of Colloidal Gold Nanoparticles during Functionalization - Dinkel, Rebecca; Jakobi, Jurij; Ziefuß, Anna Rosa; Barcikowski, Stephan; Braunschweig, Björn; Peukert, Wolfgang (Journal of Physical Chemistry C, 2018)
A molecular understanding of the ligand shell and the functionalization process is essential for the development of surface-functionalized gold nanoparticles (AuNPs). Obviously, the initial ligand shell from the synthesis plays a crucial role in this process. Here, in situ second-harmonic scattering is applied to study the adsorption of a 3-mercapto-1-propanesulfonate (MPS) at the surface of laser-ablated NaBr- and citrate-stabilized AuNPs with sizes of 5 nm. This systematic comparison is possible due to the fact that laser ablation in micromolar saline water gives access to narrowly distributed colloidal AuNPs without organic stabilizers. The Gibbs free energy of adsorption was determined to be of similar order for both AuNP batches (ca. −40 kJ/mol). The surface concentration of MPS, however, differed strongly and was more than 30% higher for NaBr-stabilized AuNP than for citrate-stabilized AuNP. Compared to planar Au substrates, the surface concentration of MPS on NaBr-AuNP suggests formation of a complete monolayer of MPS and demonstrates the fast functionalization of ligand-free AuNP up to monolayer coverage. On citrate-AuNP, however, an MPS coverage of only two-thirds of a monolayer is observed, which indicates that citrate partially resists functionalization and is mostly exchanged at low-coordinated Au surface sites. High surface coverage, however, is often closely linked to functionality, for example, when avidity effects are exploited during conjugate–receptor interaction
Keywords: Thiols; Metal nanoparticles; Adsorption; Gold; Nanoparticles